Answer:
Step-by-step explanation:
3x² - 3x + 7 = 0
a = 3 ; b = -3 and c = 7
D = b² - 4ac = (-3)² - 4*3*7
D = 9 - 84 = - 75
D = 75i²
√D = √75i² = [tex]\sqrt{5*5*3 * i * i}= 5i\sqrt{3}[/tex]
[tex]x = \dfrac{-b+\sqrt{D}}{2a} \ ; \ x=\dfrac{-b-\sqrt{D}}{2a}\\\\ \\x=\dfrac{3+5i\sqrt{3}}{6} ; \ ; x = \dfrac{3-5i\sqrt{3}}{6}\\\\\\x =\dfrac{3}{6}+\dfrac{5i\sqrt{3}}{6} ; \ ; x=\dfrac{3}{6}-\dfrac{5i\sqrt{3}}{6}\\\\\\Solution:\\\\x=\dfrac{1}{2}+\dfrac{5\sqrt{3}}{6}i ; \ ; x=\dfrac{1}{2}-\dfrac{5\sqrt{3}}{6}i[/tex]